THE INVESTIGATION OF VOICE HANDICAP INDEX IN TEACHERS WITH AND WITHOUT SELF-RATED VOICE DISORDERS - Trinite, Baiba (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
Voice disorders restrict daily activity and impact the quality of life. The purpose of the study was to find out the impact of voice disorders on functional, physical and emotional condition of teachers with and without self-reported voice disorders. Two hundred thirty-five teachers with self-reported voice problems (Voice disorder group) and 174 teachers with no voice problems (Control group) in anamnesis completed Latvian version of Voice Handicap Index-30 (VHI-30). Teachers with voice disorders demonstrated higher median scores in VHI-30 total scale and functional, physical, and emotional subscales (P<0.001). In teachers, voice disorders have a more significant impact on their physical comfort and have a smaller impact on their emotional sphere. 76.4% of the voice disorder group respondents acquired the total score within 12 to 33 points. In the control group, 75.3% of teachers had the VHI score of up to 17 points. Conclusions: In teacher population of Latvia mild voice disorders are encountered more often. Activity and participation in everyday life situations are limited in teachers with voice disorders. Voice disorders mostly impact physical comfort in teachers.